Lineage‐specific evolution of bitter taste receptor genes in the giant and red pandas implies dietary adaptation. Issue 2 (14th March 2018) - SHAN, Lei; WU, Qi; WANG, Le; ZHANG, Lei; WEI, Fuwen
Abstract: Taste 2 receptors (TAS2R) mediate bitterness perception in mammals, thus are called bitter taste receptors. It is believed that these genes evolved in response to species‐specific diets. The giant panda ( Ailuropoda melanoleuca ) and red panda ( Ailurus fulgens styani ) in the order Carnivora are specialized herbivores with an almost exclusive bamboo diet (>90% bamboo). Because bamboo is full of bitter tasting compounds, we hypothesized that adaptive evolution has occurred at TAS2R genes in giant and red pandas throughout the course of their dietary shift. Here, we characterized 195 TAS2R genes in 9 Carnivora species and examined selective pressures on these genes. We found that both pandas harbor more putative functional TAS2R genes than other carnivores, and pseudogenized TAS2R genes in the giant panda are different from the red panda. The purifying selection on TAS2R1, TAS2R9 and TAS2R38 in the giant panda, and TAS2R62 in the red panda, has been strengthened throughout the course of adaptation to bamboo diet, while selective constraint on TAS2R4 and TAS2R38 in the red panda is relaxed. Remarkably, a few positively selected sites on TAS2R42 have been specifically detected in the giant panda. These results suggest an adaptive response in both pandas to a dietary shift from carnivory to herbivory, and TAS2R genes evolved independently in the 2 pandas. Our findings provide new insight into the molecular basis of mammalian sensory evolution and the process of adaptation to new ecological niches.